Paradigmatic Model of Tacit Knowledge Sharing from the Perspective of Psychology Experts in Iranian Universities: A Grounded Theory Approach - Roudi, Gholamali; Momeni, Fateme; Mostafavi, Elham; Sagha, Fateme (KMAN Counseling & Psychology Nexus, 2026)
In the contemporary knowledge-based era, organizations—particularly universities—have become increasingly reliant on their knowledge capital. Within this context, tacit knowledge, as a hidden yet strategic resource, plays a critical role in enhancing the quality of education, research, and innovation. Unlike explicit knowledge, tacit knowledge is formed through experience, intuition, and personal skills, and is transmitted only through social interactions and human relationships. Despite the importance of this concept, academic research in Iran has largely focused on explicit knowledge, and no comprehensive model of tacit knowledge sharing from the perspective of academic psychologists has been proposed. The aim of the present study was to design a paradigmatic model of tacit knowledge sharing in Iranian universities using a grounded theory approach. This qualitative study was conducted through semi-structured interviews with psychology experts. The data were analyzed using open, axial, and selective coding, and the final model was extracted in the form of five core categories: causal conditions, contextual conditions, intervening conditions, strategies, and consequences. The results indicated that factors such as trust, motivation, interpersonal skills, organizational culture, and managerial support play a key role in tacit knowledge sharing. The outcomes of this process include the empowerment of psychologists, improved performance, increased creativity, and enhanced quality of psychological services. The findings suggest that tacit knowledge sharing is a dynamic and multi-level process shaped through the interaction between organizational structures and psychological components. By focusing on the perspectives of psychologists and integrating a psychological approach with grounded theory, this study represents a novel step toward the localization of knowledge management theories within the context of higher education in Iran.